Juridical Study of Determination of Wages for Workers based on Job Creation Act - I Wayan Merta Sukadana; Anak Agung Sagung Ngurah Indradewi (Universitas Bali Dwipa, 2022)
The enactment of Law Number 11 of 2020 concerning Job Creation makes the wage system previously regulated in Law of the Republic of Indonesia Number 13 of 2003 concerning Manpower undergo a change where the wage system which initially stated that the governor was obliged to set the minimum wage for the province became the governor to set the minimum wage. district/city with certain conditions where the use of the word “can” in determining the district/city minimum wage (UMK) is very detrimental to workers. The type of research used is normative legal research. The type of approach used is the Legislative Approach. Legal concept approach. Historical approach. The sources of legal materials used in this study are primary legal materials, secondary legal materials, and tertiary legal materials. Legal Materials Collection Techniques that the author uses in this study is a literature study data collection technique. Based on the legal materials obtained and then analyzed, then used the technique of processing legal materials in a qualitative descriptive manner. The conclusion of this study is that the regulation of the wage system in Law No. 11 of 2020 concerning job creation is the type of wages reduced where there are several points missing from the Manpower Act, the component of decent living is not included where the Job Creation Act eliminates these points in provisions for determining minimum wages and years of service are not considered in the Job Creation Act. Then the determination of the wages of workers based on article 88 c of Law No. 11 of 2020 concerning job creation only provides for the obligation to determine the minimum wage at the provincial level, while at the district/city level it is optional or optional. In fact, the provincial minimum wage is the lowest minimum wage among all district/city minimum wages in the province.